ANALYSIS OF MULTISENSORY LEARNING MEDIA NEEDS FOR CHILDREN IDENTIFIED WITH DYSLEXIA DISORDER - Sarajar, Dewita; Pratiwi, Peni (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
Learning in primary school requires proficiency in reading and writing. In practice, there are many students who experience problems in reading and writing. one of the causes is dyslexia. This research aims to analyze the form of problems experienced by students identified as dyslexic and the learning media needed by them, because students identified as dyslexic need different learning media from regular students. The research method used is a qualitative approach. The result of this research is The result of this study is that the reading learning media used by students identified as dyslexic still use the same media as regular students. The result of this study is that the reading learning media used by students identified as dyslexic still use the same media as regular students, while students identified as dyslexic need multisensory-based learning media. Multisensory media is considered appropriate because it can facilitate the needs of children with dyslexia for a richer learning experience.